Phenomenon Collaborative Management and Leadership in the Development of Traditional Village Kayu Batu City of Jayapura Indonesia - Arius Kambu (Universitas Cenderawasih, 2022)
This research aimed to examine the relationship between collaborative management, leadership, and customary authority by Ondoafi in their strategic decision-making process as traditional leaders and government figures. Information analysis was then conducted descriptively with an ethnographic basis and normative analysis, using representative leaders from the government, traditions, youth, women, and religion, as participants. The results showed that collaborative management and leadership have not been examined efficiently because informal leaders/Ondoafi also act as formal government figures in the village government system